Complement C3 and Activated Fragment C3a Are Involved in Complement Activation and Anti-Bacterial Immunity - Wu, Meng; Jia, Bei-bei; Li, Mo-fei (Frontiers in Immunology, 2022)
In the complement system, C3 is a central component in complement activation, immune defense and immune regulation. In all pathways of complement activation, the pivotal step is conversion of the component C3 to C3b and C3a, which is responsible to eliminate the pathogen and opsonization. In this study, we examined the immunological properties of C3 and its activated fragment C3a from Japanese flounder (Paralichthys olivaceus) (PoC3 and PoC3a), a teleost species with important economic value. PoC3 is composed of 1655 amino acid residues, contains the six domains and highly conserved GCGEQ sequence of the C3 family. We found that PoC3 expression occurred in nine different tissues and was upregulated by bacterial challenge. In serum, PoC3 was able to bind to a broad-spectrum of bacteria, and purified native PoC3 could directly kill specific pathogen. When PoC3 expression in Japanese flounder was knocked down by siRNA, serum complement activity was significantly decreased, and bacterial replication in fish tissues was significantly increased. Recombinant PoC3a (rPoC3a) exhibited apparent binding capacities to bacteria and Japanese flounder peripheral blood leukocytes (PBL) and induce chemotaxis of PBL. Japanese flounder administered rPoC3a exhibited enhanced resistance against bacterial infection. Taken together, these results indicate that PoC3 is likely a key factor of complement activation, and PoC3 and PoC3a are required for optimal defense against bacterial infection in teleost.